2012
DOI: 10.1186/1478-4491-10-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Sub-Saharan African medical schools

Abstract: BackgroundSub-Saharan Africa suffers a disproportionate share of the world's burden of disease while having some of the world's greatest health care workforce shortages. Doctors are an important component of any high functioning health care system. However, efforts to strengthen the doctor workforce in the region have been limited by a small number of medical schools with limited enrolments, international migration of graduates, poor geographic distribution of doctors, and insufficient data on medical schools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 6 publications
2
117
0
Order By: Relevance
“…A few universities admit large numbers of students before numbers are reduce themin the second year. Fifty nine of 84 (70%) responding schools reported that at least 80% of first-year students graduate (16).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few universities admit large numbers of students before numbers are reduce themin the second year. Fifty nine of 84 (70%) responding schools reported that at least 80% of first-year students graduate (16).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process of the review supported peer reviewers to learn from each other and share their experiences, similar to the in-country consortia of medical schools that formed within the MEPI network. [11] Medical schools in the region share common constraints of limited resources and infrastructure [12,13] and many face the challenge of finding funding for objective programme evaluations. The peer-review approach therefore affords a cost-effective mechanism to provide valuable feedback.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is also generally accepted that academic salaries for clinicians are commonly higher than they are for other academic disciplines. Thus, in a bid to attract and help retain clinicians, we negotiated a separate and enhanced salary structure with university management and the Botswana government.…”
Section: Our Approachmentioning
confidence: 99%
“…6 In addition, until 2010, eight Sub-Saharan countries had no medical schools of their own, which necessitated dependence on expatriates and external training. 7 …”
mentioning
confidence: 99%